Simultaneous removal of neonicotinoid insecticides by a microbial degrading consortium: Detoxification at reactor scale - Rodríguez Castillo, Gabriel (2019)
Neonicotinoid insecticides show high persistence in the environment, and standard biological approaches such as biopurification systems have shown mostly inefficient removal of such compounds. In this work, soil pre-exposed to imidacloprid was used to obtain presumptive imidacloprid-degrading consortia. Cometabolic enrichment yielded a microbial consortium composed of eight bacterial and one yeast strains, capable of degrading not only this compound, but also thiamethoxam and acetamiprid, as demonstrated in cross-degradation assays. The biological removal process was scaled-up to batch stirred tank bioreactors (STBR); this configuration was able to simultaneously remove mixtures of imidacloprid + thiamethoxam or imidacloprid + thiamethoxam + acetamiprid, reaching elimination of 95.8% and 94.4% of total neonicotinoids, respectively. Removal rates in the bioreactors followed the pattern imidacloprid > acetamiprid > thiamethoxam, including >99% elimination of imidacloprid in 6 d and 17 d (binary and ternary mixtures, respectively). A comprehensive evaluation of the detoxification in the STBR was performed using different biomarkers: seed germination (Lactuca sativa), bioluminescence inhibition (Vibrio fischeri), and acute oral tests in honeybees. Overall, ecotoxicological tests revealed partial detoxification of the matrix, with clearer detoxification patterns in the binary mixture. This biological approach represents a promising option for the removal of neonicotinoids from agricultural wastewater; however, optimization of the process should be performed before application in farms.